An evaluation of RBM implementation in the civil service sector in Zimbabwe - Mavhiki, Severino; Nyamwanza, Tonderai; Dhoro, Linnet (International Institute for Science, Technology and Education, 2015)
This study evaluates the reasons for failure to implement the Results Based Management (RBM) system in the public service ministries in Zimbabwe. This is against the implementation of the RBM in 2004 by the government of Zimbabwe in pursuit to improve its public performance. The new approach to management, RBM was believed to be a panacea to the challenges being faced in public sector ministries in Zimbabwe. However the RBM has been a controversial area since its inception in the public sector, with public servants not keen to implement the system. The findings indicated incentives, skills, culture, resources and performance indicators as challenges to implementation of RBM in Zimbabwean public service ministries.